Stability of breeding characters related with bread wheat quality in Southern Spain - Solís I.; Díaz M.; Alvarez J.B.; Martín L.M.; Peña R.J. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
In 1998 CIMMYT and Agrovegetal SA signed an agreement aimed at developing new wheat varieties adapted to agroclimatic conditions of Southern Spain. To select bread wheat cultivars appropriate for Andalusian market is important to meet high protein and bread making quality requirements. The stability of several characters related with bread quality of a set of five new varieties ('Escacena', 'Ecija', 'Olvera', 'Jerezano' and 'Vejer'), and three checks ('Yecora', 'Cartaya' and 'Pinzon') has been tested in samples collected from trials in quadrate lattice with three replicates in five locations of Andalusia during the 2000-2001 and 2001-2002 crop seasons. The quality testing and statistical analysis of the data were conducted at the Genetics Department of the University of Cordoba, showing that in these typical Mediterranean conditions the main part of quality parameters were highly influenced by the environment. The distribution of phenotypic variance showed that the three quality traits in which the genotype was the main factor of variation in the two-year analysis were SDSsedimentation, falling number, and alveograph-W. For the rest of traits the environment or the genotype x environment interaction explained, in at least one year, more than 50% of the observed variance.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)